Towards global sustainability: Education on environmentally clean energy technologies. (January 2018) - Nowotny, Janusz; Dodson, John; Fiechter, Sebastian; Gür, Turgut M.; Kennedy, Brendan; Macyk, Wojciech; Bak, Tadeusz; Sigmund, Wolfgang; Yamawaki, Michio; Rahman, Kazi A.
Abstract: The recent climate change agreement in Paris highlights the imperative to aggressively decarbonize the energy economy and develop new technologies, especially for the generation of electrical energy that are environmentally clean. This challenge can only be addressed by a multi-pronged approach to research and education of the next generation of scientists and engineers as well as informed public discourse. Consequently this requires the introduction of new and comprehensive education programs on sustainable energy technologies for universities and, possibly, high schools. Among others, the new programs should provide in-depth knowledge in the development of new materials for more efficient energy conversion systems and devices. The enhanced level of education is also needed for properly assessing the competing technologies in terms of their economic and social benefits. The increasing recognition of the significance of clean and efficient energy conversion indicates the need for a comprehensive education program to be developed. The purpose of the present work is to consider the structure of both an education program and the related textbook where the energy-related fundamental and applied subjects are presented in a concentrated and uniform manner. Such a textbook could be an education aid for students of energy-related courses as well as the teachers involved in the formulation of the education programs. The textbook, which should be dedicated mainly for students at the undergraduate levels at universities, and possibly high schools, should include in-depth interdisciplinary sections dedicated to energy experts and graduate students. This paper considers the present international efforts in reducing the impact of climate change and the need to develop new technologies for clean energy generation. It is argued that progress in this area requires recognition of hydrogen as the main energy carrier of the future. This work also delineates the goals of the Sustainable Energy Network, SEN, involved in the UN program of Future Earth. Highlights: Transition to global sustainability requires development of clean energy technologies. The demand of students to stablish new energy education programs is rising. There is an urgent need to produce an interdisciplinary energy textbook.